2002
DOI: 10.1161/01.atv.0000017063.36768.87
|View full text |Cite
|
Sign up to set email alerts
|

The Von Willebrand Factor Propeptide (VWFpp) Traffics an Unrelated Protein to Storage

Abstract: Abstract-The von Willebrand factor (VWF) propeptide (VWFpp) is critical for the targeting of VWF multimers to storage granules. VWFpp alone efficiently navigates the storage pathway in AtT-20 and endothelial cells and chaperones mature VWF multimers to storage granules when the two proteins are expressed in cis or in trans. To further define the role of VWFpp in granular sorting, we examined its ability to sort an unrelated protein, C3␣ into the regulated secretory pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…12,13 Our previous studies have demonstrated that VWF storage is initiated by VWFpp: VWFpp contains the "signal" for trafficking to granules and secondarily cotraffics mature VWF by virtue of a noncovalent association. 14,15 However, VWF granular storage and multimerization have also been shown to be independent processes: multimerization is not necessary for granular storage. 12,[15][16][17] Here we report the characterization of a Turkish consanguineous family diagnosed with type 2A VWD.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Our previous studies have demonstrated that VWF storage is initiated by VWFpp: VWFpp contains the "signal" for trafficking to granules and secondarily cotraffics mature VWF by virtue of a noncovalent association. 14,15 However, VWF granular storage and multimerization have also been shown to be independent processes: multimerization is not necessary for granular storage. 12,[15][16][17] Here we report the characterization of a Turkish consanguineous family diagnosed with type 2A VWD.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Previous studies in our laboratory have demonstrated that VWF is sorted to regulated storage vesicles in a VWFpp-dependent manner. 19,20 Our studies were carried out using the mouse pituitary model cell line AtT-20 and bovine aortic endothelial cells (BAECs) that have endogenousregulated storage granules containing adrenocorticotrophic hormone (ACTH) or bovine VWF, respectively. We have demonstrated that the propeptide independently sorts to endogenous storage granules in these cells and co-traffics mature VWF multimers through a noncovalent association.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the propeptide independently sorts to endogenous storage granules in these cells and co-traffics mature VWF multimers through a noncovalent association. 19,21 However, because of the presence of endogenous-regulated secretory vesicles, these studies could not address the biogenesis of the regulated storage vesicle.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the mean t1/2 value of VWFpp after DDAVP administration in the patients was 100 min (range: 85-115 min) which is shorter than that previously reported in normal individuals (2-3 h). [16][17][18] Some temporary correction of VWF:RCo/VWF:Ag and VWF:CB/VWF:Ag ratios was observed ( Figures 3E and F). Noticeable quantitative differences were seen among the three families of patients.…”
Section: Resultsmentioning
confidence: 99%